Evaluating the Landscape of Public Finance Studies in Azerbaijan: Qualitative Data Analyses of the Expert Interviews - Niftiyev, Ibrahim (Public Finance Quarterly, 2025)
Public finance is both an academic and a social issue when it comes to oil-rich countries where transparency and institutional checks and balances are yet established due to the Dutch disease and the curse of natural resources. Typically, some econometric and statistical research papers show the big picture but fail to contextualize the deeper issues behind the challenges of public finance in such countries. The aim of this study is to conduct a systematic and detailed analysis of expert opinions to examine the state of academic studies on public finance using the example of Azerbaijan—a small, open economy rich in oil and natural gas. To achieve this goal, thirty structured email interviews were collected and analyzed using qualitative data analysis (QDA) methods such as thematic analysis (TA), cooccurrence analysis, word cloud visualization and reflective writing. The QDA results revealed that the current state of academic studies does not cover the comprehensive scientific analysis of public finance in Azerbaijan in the expected way; transparency and accountability are the main institutional barriers that need to be studied in the context of public finance; the optimality and efficiency of state budget expenditures and revenues need to be analyzed along with policy reforms to achieve fiscal sustainability in the near future. These findings shed a unique light on a rarely analyzed topic that may be of interest to policy makers and academics, providing an alternative to the traditional literature reviews and bibliometric studies in this direction.